Alternative coarse agregate using locally available materials in Bangkalan - Pertiwi, Dewi; Agusdini, Theresia Maria; Farchan, Muchamad (Jurnal IPTEK, 2024)
Madura Island possesses significant natural resources, particularly aggregates from class C excavations in Bangkalan Regency. These aggregates, including fine aggregate (sand) and coarse aggregate (gravel), are potential materials for concrete mixtures. However, concrete produced solely with Bangkalan aggregates typically achieves a compressive strength of 14 MPa. Combining these aggregates with those from Java Island can enhance compressive strength to 20 MPa. This study aims to determine the optimal composition of Bangkalan and Pandaan coarse aggregates, using admixtures type D (0.3%) and type F (0.6%), to achieve a target compressive strength of 35 MPa. Various combinations of coarse aggregates (100% Bangkalan, 90% Bangkalan and 10% Pandaan, 80% Bangkalan and 20% Pandaan, and 70% Bangkalan and 30% Pandaan) were tested using cylindrical specimens (15 x 30 cm). The results indicate that the combination of 90% Bangkalan and 10% Pandaan aggregates, with the specified admixtures, produced the highest compressive strength of 31.06 MPa at 28 days, which did not meet the target of 35 MPa. This suggests further research is needed to explore additional aggregate combinations and admixture variations to achieve the desired compressive strength.